Kehadiran Media Sosial Dan Partisipasi Politik Bagi Pemilih Pemula - El Farabi, Qoryna Noer Seyma (Universitas Al Azhar Indonesia, 2022)
The development of the times was followed by the development of technology and forms of communication at this time. Social media is emerging as a new media platform in various fields, including politics. Beginner voters are new voters who are involved in political activities and who use social media for various activities related to their politics. Starting from looking for information to opening a discussion. Beginner voters who are still in the category of teenagers today cannot be separated from the presence of social media, so social media has a big influence on their political participation. The researcher tries to analyze the phenomenon of social media and political participation for beginner voters. This study uses qualitative methods, by conducting interviews to obtain data. The results of this study are that social media provides space for beginner voters to express themselves and create their identity, without having to reveal their real identity or be anonymous, and it provides new connections and social groups to open up new voters' views on politics without any boundaries.